Serum immunoglobulins and anti-pneumococcal antibody levels in patients with bronchiectasis of unknown aetiology (Bangladesh Journal of Medical Science, 2020)
Background: Bronchiectasis is a chronic condition which can result in significant physical and social morbidity. The exact prevalence in Malaysia is unknown although several studies have shown a higher prevalence in the Asian population. Several causative factors have been identified but there are many patients with unknown aetiologies. This study looks into the level of serum immunoglobulins and antipenumococcal antibody in bronchiectasis patients where they were not part of prior routine investigations.Methodology: Four hundred fifteen bronchiectasis patients were screened and 26 patients who fulfilled the inclusion and exclusion criteria were enrolled for this study. The serum immunoglobulins (IgG, IgA and IgM) concentrations were measured using nephelometry and interpreted according to age-matched reference range. The integrity of antibody production against specific antibody to capsular polysaccharides of Streptococcus pneumoniae were assessed using ELISA method and the level of ≥ 10mg/L is considered as reactive.Results: The twenty six bronchiectasis patients have the mean age of 62 years and a predilection of female gender. Majority of patients presented with typical bronchiectasis symptoms which were further supported by radiological findings. One of 26 patients (4%) had low total serum IgG level. The vaccinated group has higher anti-pneumococcal capsular polysaccharide antibody level (median: 224.2 mg/L) compared to the unvaccinated group (median: 100.4 mg/L). However there is no statistical difference between the anti-PCP levels of both groups (p> 0.05). All of the selected patients had reactive specific antibody to capsular polysaccharides of Streptococcus pneumoniae regardless of the vaccination status, which may reflect the natural acquisition of anti-pneumococcal immunity.Conclusion: Although immunoglobulin deficiency is an uncommon aetiological cause of bronchiectasis, the immunoglobulin parameters can be helpful in selecting patients who should receive the appropriate treatment of immunoglobulin therapy for the prevention of subsequent complications and better quality of life.Bangladesh Journal of Medical Science Vol.19(2) 2020 p.200-207